BUYING AND SELLING TRANSACTIONS WITH SHOPEE PAYLATER PERSPECTIVE OF SHARIA ECONOMIC LAW - Sofian Syaiful Rizal; Hasan Baharun (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The very rapid development of technology makes all buying and selling transactions carried out not have to be face to face. Then buying and selling in Islamic law is often referred to as buying and selling online, which is actually permissible in modern fiqh as long as the pillars and conditions are met when it does not involve usury, gharar and maisir because basically all buying and selling must avoid these things. This study analyzes the review of Islamic law regarding buying and selling online with Shopeepay Later Credit. The data analysis technique in this study is descriptive qualitative. The results of this research analysis show that: The practice of Shopeepay Later transactions is carried out through an application, namely through the Shopee marketplace, when Shopee users register for Shopeepay Later activation. After Shopeepay Later is successfully activated, users can use Shopeepay Later to shop, and users can pay for their purchases according to the tempo They selected. The way to pay bills can be done by transferring via ATM, I-Banking, M-Banking or paying through minimarkets such as Indomaret and Alfamart. According to Islamic law, Shopeepay Later, when viewed from the pillars and terms of buying and selling, the pillars of qard are in accordance with Islamic law. Then, if seen from DSN-MUI No: 110/DSN- MUI/IX/2017 regarding the sale and purchase contract, it is permissible that the non-cash sale and purchase price may not be the same as the cash price, so the price difference is on Shopeepay Later to buy now, pay later, 3x instalments, 6x instalments and 12x instalments are allowed. Buying and selling Shopeepay Later is justified by buying and selling greetings. That is, both buying and selling are delayed on greetings for goods that are delayed, while on Shopeepay Later, the money is delayed. However, the fine that applies as much as 5% when late paying is usury